Identifying Opportunities and Threats of Tourism Destinations in Pancuran 13 and Curug Serwiti, Guci Tegal, Central Java - Muafi, Muafi; Nursyamsiah, Siti; Hidayat, Anas; Arundati, Rahajeng; Purnama, Rava Fernanda; Sabellah, Ria Eka; Andestari, Yonada; Suhada, Suhada; Tamara, Karima; Yustiani, Sofia; Veisz, Adrienn; Huszár, Barbara (Asian Journal of Community Services, 2024)
This community service activity aims to identify opportunities and challenges for the Curug Serwiti tourist park in Guci Tegal, Central Java. As tourist destinations, Pancuran 13 and Curug Serwiti are managed by Berkah Tirta Guci, a village-owned enterprise. The focus of activities is directed at identifying opportunities and threats in developing these two destinations. This community service activity have been carried out well, which are indicated by: (1) the number of participants and SMEs involved was 100%, (2) increased knowledge and insight related to village-owned enterprise management, especially in managing tourist destinations, (3) gained knowledge related to motivation endeavor, (4) publication in scientific journals to identify opportunities and threats as well as provide policy recommendations.